2014
DOI: 10.1007/s12298-014-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

PGPR regulate caspase-like activity, programmed cell death, and antioxidant enzyme activity in paddy under salinity

Abstract: The response of two root associated bacteria Pseudomonas pseudoalcaligenes and Bacillus pumilus were studied in the (salt-sensitive) rice GJ17 cultivar to salinity under controlled environmental growth conditions for protection of plant from adverse effect of salinity. Salinity affects the growth of salt-sensitive cultivar, but inoculation of plant growth promoting rhizobacteria (PGPR) reduces the harmful effect of salinity. The present study states that PGPR helps to reduce lipid peroxidation and superoxide d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(69 citation statements)
references
References 33 publications
4
59
0
1
Order By: Relevance
“…The lipid peroxidation showed significant decrease in all the PGPR inoculated and PGR treated plants. Jha and Subramanian (2014) found that inoculation with a single PGPR reduced the lipid peroxidation by 1 time while, combination of 2 PGPR reduced the content up to 1.6 time under salt stress condition. Koc (2015) also reported the negative impacts of plant growth promoting bacteria and arbuscular mycorrhizal fungi on lipid peroxidation and total phenolics of strawberry when grown under stress condition.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The lipid peroxidation showed significant decrease in all the PGPR inoculated and PGR treated plants. Jha and Subramanian (2014) found that inoculation with a single PGPR reduced the lipid peroxidation by 1 time while, combination of 2 PGPR reduced the content up to 1.6 time under salt stress condition. Koc (2015) also reported the negative impacts of plant growth promoting bacteria and arbuscular mycorrhizal fungi on lipid peroxidation and total phenolics of strawberry when grown under stress condition.…”
Section: Discussionmentioning
confidence: 92%
“…The observed reduction of antioxidant enzymes by the PGPR treatment may be attributed to the fact that PGPR reduced the occurrence of stress induced oxidative stress in plants subsequently the antioxidant enzymes were lesser in PGPR/PGR heated plants. SOD activity was higher in paddy due to salt stress but inoculation of PGPR decreased the SOD activity (Jha and Subramanian 2014). Khan et al (2017) reported that the combined application of PGPR lead to significant decrease in CAT, POD and SOD activities in the leaves of chickpea grown under stress conditont.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamines secreted by PGPR have also been exposed to mitigate stress ethylene levels and alleviate osmotic stress [30,31]. PGPR have been demonstrated to activate the synthesis of antioxidants and indole acetic acid, which can stimulate root growth [28,32,33]. Recently, PGPR were shown to alter mineral uptake, which results in a favorable increase in the cellular ratio of K+/Na+; and elevated generation of quorum-sensing molecules, which can lead to modifications in the rhizosphere [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Although PGPR application reduced the MDA concentration, maximum reduction (by 39 %) was recorded with combination treatment at both the salt stress conditions. Lower MDA concentration represents less membrane damage or increased salt tolerance of the plants (Jha and Subramanian 2014).…”
Section: Discussionmentioning
confidence: 99%